Zeolit Sintetis Terfungsionalisasi 3-(Trimetoksisilil)-1-Propantiol sebagai Adsorben Kation Cu(II) dan Biru Metilena - Sri Sugiarti; Charlena Charlena; Nurul Afiati Aflakhah (Syarif Hidayatullah State Islamic University, 2017)
The more commonly used method for making synthetic zeolite from kaolin is hydrothermal method. This research tested a sol-gel method in processing synthetic zeolit using kaolin as the basic ingrediant. The synthetic zeolite derived from the sol-gel method was then characterized using X-ray Difractometer and Scanning Electron Microscope, which found resulting products zeolite-A, zeolite Y and sodalite. The adsorption ability of the synthetic zeolites was tested using Cu(II) and methylene blue. Functionalization of the synthetic zeolites by 3-(trimetoksisilil)-1-propantiol was done to increase adsorption capacity. Zeolite A modified by 3-(trimetoksisilil)-1-propantiol had the greater capacity to adsorb methylene blue at 30.11 mg/g. The adsorption isotherms of all the synthetic zeolites approached the Langmuir form. The adsorption energy off all synthetic zeolites approached the chemical adsorption.DOI: http://dx.doi.org/10.15408/jkv.v0i0.5144